EXPLORING THE PROGRESSIVE LAW IN THE CONSTITUTIONAL COURT DECISION NO. 93/PUU-X/2012 ON TESTING ARTICLE 55 VERSES (2) AND (3) LAW NO. 21 OF 2008 CONCERNING SHARIA BANKING - Ahmad Syarifudin (Universitas Islam Negeri Mataram, 2019)
After the Constitutional Court issued decision No. 93/PUU-X/2012 for testing Article 55 paragraph (2) and (3) of Law No. 21 of 2008 concerning Sharia Banking to Article 28D paragraph (1) of the 1945 Constitution, the Religious Court has regained its authority to settle Islamic banking disputes. In the ruling, the Constitutional Court stipulates that the explanation of Article 55 paragraph (2) is contrary to the 1945 Constitution, and at the same time does not have binding legal force. The cause of the unconstitutionality occurs because the explanation of Article 55 paragraph (2) of the a quo law contains several dispute resolution forums, namely deliberation, banking mediation, National Sharia Arbitration Board or other arbitration and through a general court which makes the court conclude it will cause uncertainty because of the Paragraph (1) has clearly mentioned the Religious Court. This paper wants to know the urgency of progressive law in the Constitutional Court's decision No. 93/PUU-X/2012 also wants to know whether in the Constitutional Court's decision No. 93/PUU-X/2012 has implemented progressive laws.